Analysis of Philippine rice policy - Defiesta, Gay (Danyag :the UPV journal of humanities and social sciences, 2002)
"Government control in the rice sector dates back to colonial period. The instruments used varied but intervention was sustained over time. The current policy is a two-tiered scheme with the goals of ensuring enough supply, making prices affordable to the poor consumers and extending assistance to farmers. The National Food Authority is the central organization through which the Philippine government regulates the price, marketing and trade of rice. After the long years of intervention, rice farming in the Philippines remains small scale, traditional and less productive compared to other Asian countries. Moreover, poverty in the rural areas where small rice farmers and laborers live is still high. Evidently, the protection did not have that much effect on the sector. The policy should be reassessed and reoriented to alleviate the condition of the groups to which it is intended for."